(3caGjI GdeMJGL deYQaI ef djS aj GdOjHGLs - (3CHh GdYHGS CMeO Hf CMeO Hf YeQ Hf eMeO HGHG GdJfHcJi GdShOGfi GdeGdcjs; (3GdJfHcJj , CMeO HGHG Hf CMeO Hf CMeO Hf YeQ GdJcQhQj GdShOGfj, CHh GdYHGS,J (B1036 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdJSdje YdiSjOfG eMeO SjO GdeQSdjf s
(3fbdkG Yf fSNI GdeUfas
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B102 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B145s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B122 s
Keywords: (3GdJGQjNs